Efficacy and Maternal Hemodynamic Response of Nifedipine versus Hydralazine in the Management of Severe Pregnancy-Induced Hypertension: A Comparative Study - Sajida Imran, Munawar Afzal, Humaira Tahir, Ibtisam Nawaz Minhas, Maryam Shoaib, Syeda Shaista Waheed, Sundos Suleman Ismail Abdalla, (Pakistan Journal of Medical & Health Sciences, 2023)
Aims and Objectives: The purpose of this study was to compare nifedipine to hydralazine with respect to efficacy, maternal hemodynamic response, and fetal outcomes in severe pregnancy induced hypertension. The aim was to assess the safety of antihypertensive agents in the treatment of hypertensive emergencies in pregnancy with regard to BP control and adverse effects during pregnancy. Methodology: Total n=100 participants were considered in this study, the pharmacological effects of nifedipine in comparison with hydralazine were compared in the treatment of severe pregnancy induced hypertension (PIH). It measured time to BP ≤150/100 mmHg, BP changes, heart rate and adverse events. Fetal outcome included heart rate abnormalities, APGAR scores, and NICU admissions. Treatment efficacy, safety and requirements for further therapy were also studied to determine an appropriate antihypertensive treatment in pregnancy. Results: BP control was faster with nifedipine than with hydralazine (34.8 ± 7.5 vs. 42.1 ± 8.3, p = 0.008) and more patients achieved target BP (89.2% vs. 76.5%, p = 0.03). In addition, it resulted in more smooth BP reduction without more hypotension (2.3% vs. 5.2%, p = 0.04) and less reflex tachycardia (3.4% vs. 7.6%, p = 0.03). Nifedipine was associated with better neonatal outcomes (NICU admissions 10.3% vs. 15.6%, p = 0.04 and fewer fetal heart rate abnormalities). In general, nifedipine was better and safer than hydralazine for the treatment of severe PIH. Conclusion: In severe pregnancy induced hypertension, hydralazine was compared to nifedipine and nifedipine was superior as it had better efficacy, faster BP control, better maternal hemodynamic stability, and better fetal outcomes. It should be regarded as the first line antihypertensive agent for the management of hypertensive emergencies in pregnancy. Keywords: Pregnancy induced hypertension, Hydralazine, Nifedipine, Fetal, Antihypertensive.